The Macroeconomic Conditions of the Remuneration and Pension Dynamics in Poland (2010–2035) - Ochocki, Andrzej (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
The aim of the article is to indicate the macroeconomic conditions which determined the dynamics of remuneration and pension growth in Poland in 2010–2019, along with presenting the study forecast until 2035. The research was based on the data from the national accounts, population statistics, statistics of retirement benefits, demographic forecast of Statistics Poland and forecast of retired population worked out by ZUS. The demographic ageing of society leads to the growing problem of distribution of the current stream of goods and services produced in the economic process. The possibilities in this respect are determined by the relations between dynamics of the number of employed persons, number of pensioners and the volume of national income. The resulting dependencies can be described using the Intergenerational Income Transfer Model (IITM). The observation of tendencies in Poland demonstrated that the pace of GDP growth between 2010–2019 ensured the macroeconomic balance essential in the process of shaping remunerations and pensions – GDP was growing faster than remunerations and pensions. The carried out estimates indicate the need to maintain a GDP growth rate and productivity at not less than 2% per annum, which means that the volume of GDP will need to increase by more than 12% in 2025 compared to 2019 (using IITM). With the help of the IITM it was also possible to identify the main difficulty facing the public intergenerational transfers, which in a state perceived as a common good, should be understood as pensioners’ liabilities and their repayment should ensure a fair standard of living for the elderly.